Phylogenomic Analysis of Dichrocephala benthamii and Comparative Analysis within Tribe Astereae (Asteraceae) - Hui Chen; Tingyu Li; Xinyu Chen; Xinyi Zheng; Tianmeng Qu; Bo Li; Zhixi Fu (Genetics and Molecular Biology)
Abstract Dichrocephala benthamii C. B. Clarke has long been used as traditional Chinese medicine. However, the chloroplast (cp) genome of D. benthamii is poorly understood so far. In this study, we sequenced and analyzed the cp genome of D. benthamii. The results showed that the cp genome is 152,350 bp in length, with a pair of inverted repeat regions (IRa and IRb, each 24,982 bp), a large single-copy (LSC) region comprising 84,136 bp, and a small single-copy (SSC) region comprising 18,250 bp. The GC content of the cp genome was 37.3%. A total of 134 genes were identified, including 87 protein-coding genes (CDS), 38 tRNA genes, 8 rRNA genes, and 1 pseudogene (ycf1). Expansion or contraction of IR regions were detected in D. benthamii and other species of the tribe Astereae. Additionally, our analyses showed the types of sequence repeats and the highly variable regions discovered by analyzing the border regions, sequence divergence, and hot spots. The phylogenetic analysis revealed D. benthamii is the basal group of Astereae. The results of this study will be a significant contribution to the genetics and species identification related to D. benthamii.